Biology of stem cells and the molecular basis of the stem state - Zipori, Dov. (Stem cell biology and regenerative medicine, 2009)
Biology of Stem Cells and the Molecular Basis of the Stem State concentrates upon adult stem cells, particularly on mesenchymal cell populations, which are the author’s area of expertise. The text offers the reader a detailed description of the emergence of stem cell research and the dogmas that were created during the first decades of analysis of stem cell properties, particularly those of hemopoietic stem cells. Biology of Stem Cells and the Molecular Basis of the Stem State also introduces the reader to the commonly accepted notions regarding stem cell biology, with an emphasis on an alternative view of stemness, i.e. the stem state. In keeping with the popularity of this topic, Biology of Stem Cells and the Molecular Basis of the Stem State addresses the major controversies and points of dispute, among researchers in the stem cell field. Overall, Biology of Stem Cells and the Molecular Basis of the Stem State presents a well-rounded dialogue about stem cells as it not only concentrates upon the biological elements of stem cell, but also addresses the controversy and hype currently enveloping this popular subject. Historical Roots -- Multipotency and Tissue-Specific Stem Cells -- Stem Cells with No Tissue Specificity -- Stem Cell Niches -- A Critical Analysis of Properties Commonly Ascribed to Stem Cells -- The Stem State: Stemness as a State in the Cell’s Life Cycle -- The Stem State in Cancer -- MSC Therapy in Animal Models and in Regenerative Medicine for Human Diseases.